Ritmos Brasileiros utilizados em composições para Drumline - Carmo, Ítala Natali Nantes Ferreira do (2020)
In the present work, the adaptations of Brazilian Rhythms in compositions for Drumline are presented as the main objective of the research. The aim is to understand and develop ways to make these adaptations. The Drumline is the section of the percussion instruments of the Marching Bands and Drum & Bugle Corps and can be a stand-alone unit. This dissertation is organized in four chapters. The first chapter deals with a panoramic view of Marching Bands, trying to situate the reader in this wide universe. We also present the Drumlines, showing their structure, technique and Rudiments. In the second chapter, we present the Martial Bands in Brazil. We also trace the Drumline origins in Brazil. In the third chapter, the Brazilian Rhythms that were used for the compositions of the pieces are discussed, we briefly present their characteristics, origins and instrumentation. In the fourth and last chapter we will describe the compositions for Drumline using Brazilian rhythms.